Tuning of multiple luminescence outputs and white-light emission from a single gelator molecule through an ESIPT coupled AIEE process. Issue 11 (24th December 2014) - Maity, Arunava; Ali, Firoj; Agarwalla, Hridesh; Anothumakkool, Bihag; Das, Amitava
Abstract : A single gelator molecule (1 ) shows an ESIPT coupled AIEE process for generating multiple luminescent colors, including white-light, with varying aggregation as a function of the water content in a THF–water mixture. Luminescent property of1 is retained in gel as well as in solid state. Abstract : A unique example of an ESIPT coupled AIEE process, associated with a single molecule (1 ), is utilized for generating multiple luminescent colors (blue-green-white-yellow). The J-aggregated state of1 forms a luminescent gel in THF and this luminescent property is retained even in the solid state.